Effects of exogenous C18 unsaturated fatty acids on milk lipid synthesis in bovine mammary epithelial cells. Issue 3 (7th August 2020) - Zhang, Hang; Dan, Ni; Ao, Changjin; Wang, Sizhen; Erdene, Khas; Ashraf, Mohammed Umair
Abstract: We determined the effects of a combination of C18 unsaturated fatty acids (C18-UFAs) consisting of oleic, linoleic, and linolenic acids on milk lipogenesis in bovine mammary epithelial cells (BMECs) . By orthogonal experiments to determine cellular triacylglycerol (TAG ) accumulation, a combination of 200 μmol/l C18 : 1, 50 μmol/l C18 : 2, and 2 μmol/l C18 : 3 was selected as C18-UFAs combination treatment, and culture in medium containing fatty acid-free bovine serum albumin was used as the control. The expression of genes related to milk lipid synthesis and intracellular FA composition was measured. The results showed that cytosolic TAG formation was higher under C18-UFAs treatment than under control treatment. The mRNA expression of acetyl-CoA carboxylase - α ( ACACA ), fatty acid synthase ( FASN ), and peroxisome proliferator-activated receptor gamma ( PPARG ) did not differ between treatments. The abundance of stearoyl-CoA desaturase ( SCD ) and acyl-CoA synthetase long-chain family member 1 ( ACSL1 ) was higher, whereas that of sterol regulatory element binding transcription factor 1 ( SREBF-1 ) was lower after C18-UFAs treatment compared to control treatment. The C16 : 0 and SFA content was decreased following C18-UFAs treatment compared to control treatment, while the cis -9 C18 : 1 and UFA content was increased. In conclusion, C18-UFAs could stimulate triglyceride accumulation, increase the cellular UFA concentration, and regulate lipogenic genes in BMECs.